Attitudes towards clinical research among cancer trial participants and non-participants: an interview study using a Grounded Theory approach. Issue 4 (30th March 2007) - Madsen, S M; Holm, S; Riis, P
Abstract : The attitudes of women patients with cancer were explored when they were invited to participate in one of three randomised trials that included chemotherapy at two university centres and a satellite centre. Fourteen patients participating in and 15 patients declining trials were interviewed. Analysis was based on the constant comparative method. Most patients voiced positive attitudes towards clinical research, believing that trials are necessary for further medical development, and most spontaneously argued that participation is a moral obligation. Most trial decliners, however, described a radical change in focus as they faced the actual personal choice. Almost no one got an impression of clinical equipoise between treatments in the trials, and most patients expressed discomfort with randomisation. A patient's choice to participate was mainly determined by whether the primary focus was on treatment effect or on adverse effects. Both knowledge about and feelings towards trials originated mostly from the media, although paradoxically the media were largely seen as untrustworthy. Mistrust was shown towards the pharmaceutical industry, and although most patients originally trusted that doctors primarily pursued the interest of patients, they did not trust the adequacy of doctors or industry in maintaining self-regulation. Thus, public control measures were judged to be essential.